Discovery of a new pyrimidine synthesis inhibitor eradicating glioblastoma-initiating cells. Issue 2 (10th September 2019) - Echizenya, Smile; Ishii, Yukiko; Kitazawa, Satoshi; Tanaka, Tadashi; Matsuda, Shun; Watanabe, Eriko; Umekawa, Masao; Terasaka, Shunsuke; Houkin, Kiyohiro; Hatta, Tomohisa; Natsume, Tohru; Maeda, Yoshimasa; et al.
Abstract: Background: Glioblastoma-initiating cells (GICs) comprise a tumorigenic subpopulation of cells that are resistant to radio- and chemotherapies and are responsible for cancer recurrence. The aim of this study was to identify novel compounds that specifically eradicate GICs using a high throughput drug screening approach. Methods: We performed a cell proliferation/death-based drug screening using 10 560 independent compounds. We identified dihydroorotate dehydrogenase (DHODH) as a target protein of hit compound 10580 using ligand-fishing and mass spectrometry analysis. The medical efficacy of 10580 was investigated by in vitro cell proliferation/death and differentiation and in vivo tumorigenic assays. Results: Among the effective compounds, we identified 10580, which induced cell cycle arrest, decreased the expression of stem cell factors in GICs, and prevented tumorigenesis upon oral administration without any visible side effects. Mechanistic studies revealed that 10580 decreased pyrimidine nucleotide levels and enhanced sex determining region Y–box 2 nuclear export by antagonizing the enzyme activity of DHODH, an essential enzyme for the de novo pyrimidine synthesis. Conclusion: In this study, we identified 10580 as a promising new drug against GICs. Given that normal tissue cells, in particular brain cells, tend to use the alternative salvage pathway for pyrimidine synthesis, our findings suggest that 10580 can be used for glioblastoma therapy without side effects. Key Points 1. Chemical screening identified 10580 as a novel GIC-eliminating drug that targets DHODH, an essential enzyme for the de novo pyrimidine synthesis pathway. 2. Compound 10580 induced cell cycle arrest, apoptosis, and differentiation in GICs.